Photography tele-transmission by regular ambulance staff for the management of mild traumatic injury: the NiCEPHORE randomised-controlled trial - E. Magimel-Pelonnier; N. Marjanovic; R. Couvreur; B. Drugeon; O. Mimoz; J. Guenezan (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2022)
Abstract Background Handling emergency calls in French emergency medical call centres (EMCCs) can be challenging considering the frequent lack of relevant information. Tele-transmission device use in regular ambulances seems like a good solution to provide the EMCC physician with a more accurate assessment of the scene, particularly for mild traumatic injury (MTI). We measured the impact of ambulance staff tele-transmitted photography on prehospital dispatching optimisation for patients calling the EMCC with MTI. Methods We conducted a prospective, single-centre, randomised-controlled trial comparing two groups of patients calling the EMCC with MTI who were or were not allocated to photography tele-transmission by ambulance staff. The primary outcome was the proportion of patients referred away from the nearest hospital (left at home for outpatient care; referred to a higher-level hospital; handled by a medical intensive care ambulance for advanced pre-hospital care) used as a marker of better orientation. Results Between 29 April 2019 and 21 July 2020, 165 patients were randomised and 152 analysed. Photography tele-transmission resulted in better patient dispatching (24/73 [33%] patients in the intervention group vs 9/79 [11%] patients in the control group, OR 3.80 [1.63–8.90]; p = 0.03), without increasing the proportion of patients initially left at home for outpatient care and visiting an ED within 10 days for secondary trauma-related care (1/14 [7%] vs 1/4 [25%], OR 0.25 [0.01–24.1]; p = 0.41). The proportion of patients unnecessarily referred to an ED was 7% [4/59 patients] in the intervention group vs 16% [12/75 patients] in the control group (OR 0.38 [0.09–1.36]; p = 0.10). Conclusion Photography tele-transmission by regular ambulance staff could improve the dispatching of patients calling French EMCCs with MTI. Trial registration The study is registered with Clinicaltrials.gov (NCT04034797).